Enolate-directed catalytic C–H functionalization of 2-aryl-1,3-dicarbonyl compounds - Khan, Imtiaz (2015)
I) Synthesis of Spiroindenes by Enolate-Directed Ruthenium-Catalyzed Oxidative Annulation of Alkynes with 2-Aryl-1,3-dicarbonyl Compounds The synthesis of carbocycles by the ruthenium-catalyzed oxidative annulation of alkynes with 2-aryl cyclic 1,3-dicarbonyl substrates is described. Proceeding by the functionalization of C(sp3)–H and C(sp2)–H bonds, and the formation of all-carbon quaternary centers, the reactions provide a diverse range of spiroindenes in good yields and high levels of regioselectivity. II) Synthesis of Benzopyrans by Pd(II)- or Ru(II)-Catalyzed C–H Alkenylation of 2-Aryl-3-hydroxy-2-cyclohexenones We have explored the 2-aryl-3-hydroxy-2-cyclohexenones as competent substrates for palladium- and ruthenium-catalyzed C–H alkenylation reactions with terminal alkenes. This process affords benzopyrans, in most cases, with good functional group tolerance. III) Synthesis of Spiroindanes by Palladium-Catalyzed Oxidative Annulations of 1,3-Dienes Involving C–H Functionalization 1,3-Dienes have been an underexplored class of substrates in catalytic oxidative annulation reactions involving C‒H functionalization. The synthesis of spiroindanes by the palladium-catalyzed oxidative annulation of 1,3-dienes with 2-aryl cyclic 1,3-dicarbonyl compounds is described. Several examples of the dearomatizing oxidative annulation of 1,3-dienes with 1-aryl-2-naphthols are also presented. IV) Enantioselective Spiroindene Formation via C‒H Functionalization Using Chiral Cyclopentadienyl Rhodium Catalysts A chiral cyclopentadienyl rhodium ligand with an atropchiral biaryl backbone enables an asymmetric synthesis of spiroindenes from 2-aryl-1,3-dicarbonyl compounds and alkynes. The process affords a range of products with all-carbon quaternary center in high yields and excellent enantiselectivities. The good functional group tolerance and broad substrate generality are the advantages of this reaction.